Taurine supplementation improves economy of movement in the cycle test independently of the detrimental effects of ethanol - Paulucio, Dailson; Costa, Bruno M.; Santos, Caleb G. M.; Nogueira, Fernando; Koch, Alexander; Machado, Marco; Velasques, Bruna; Ribeiro, Pedro; Pompeu, Fernando AMS (Biology of Sport, 2017)
Taurine (TA) ingestion has been touted as blunting the deleterious effects of ethanol (ET) ingestion on motor performance. This study investigated the effects of ingestion of 0.6 mL·kg-1of ET, 6 grams of TA, and ethanol in combination with taurine (ET+TA) on economy of movement (EM) and heart rate (HR). Nine volunteers, five female (22 ± 3 years) and four male (26 ± 5 years), participated in a study that used a counterbalanced experimental design. EM and HR were measured for 6 min while the subjects were pedalling at a fixed load 10% below the anaerobic threshold. The blood alcohol concentration (BAC) was similar between ET and ET+TA treatments at 30 min after ingestion and after exercise (12.3 mmol·L-1 vs. 13.7 mmol·L-1, and 9.7 mmol • L-1 vs 10.9 mmol·L-1, respectively). EM was significantly different among treatments, with lower mL·W-1 following ingestion of TA (-7.1%, p<0.001) than placebo and ET+TA (-2.45%, p=0.001) compared to ET. HR (bpm) was significantly (p<0.05) higher for ET (137 ± 14 bpm) than the other three treatments (placebo = 129 ± 14 bpm; TA = 127 ± 11 bpm; TA+ET = 133 ± 12 and ET = 137 ± 14 bpm). Taurine improved EM when compared to placebo or ET, and reduced HR when compared to ET. The combination of ET+TA also enhanced EM compared to placebo, and reduced HR in comparison to ET alone. Therefore, these findings indicate that taurine improves EM and counteracts ethanol-induced increases in HR during submaximal exercise.